Design of an integrated circuit for speaker independent isolated word speech recognition - Teh, Chih Chiang. (2008)
This thesis documents the development of the IC, including the details of the recognition algorithm, the design of the algorithm on VHDL code, the layout realization with standard cells and the verification at each design stage. The IC is aimed for speaker independent, small vocabulary and isolated words recognition.